Investigation of the antimicrobial mode of action of sodium acid sulfate and potassium acid sulfate. (August 2021) - McDaniel, Conner; Teng, Xin Mei; Jaroni, Divya; Jadeja, Ravi
Abstract: This study aims to identify the antimicrobial mode of action of sodium acid sulfate (SAS) and potassium acid sulfate (KAS) against three major foodborne pathogens, Escherichia coli O157:H7, Salmonella Typhimurium DT 104, and Listeria monocytogenes . The overnight grown cultures of the target pathogens were subjected to SAS and KAS treatments to identify the minimum inhibition concentrations of each antimicrobial. The impact of SAS and KAS treatments on the target pathogens at bio-molecular levels was also studied. To help determine if the mode of action is pH-driven, SAS and KAS's antimicrobial efficacies were also compared against hydrochloric acid (HCL). The MIC values of SAS and KAS for all three pathogens were 7.5 mg/mL while for HCL, the MICs were greater than 30 mg/mL. Similarly, SAS and KAS treatments resulted in more damage to all target pathogens and increased leakage of nucleic acid, protein, and ions than HCL treatments. Transmission electron microscope images also revealed that 7.5 mg/mL SAS and KAS treatments resulted in significantly more visible cell damage in S. Typhimurium and E. coli O157:H7 than HCL treatments. The study's findings indicate that the SAS and KAS could be the function of pH, oxidation of cell components, and osmolarity. Highlights: Antimicrobial mode of action of sodium acid sulfate and potassium acid sulfate were determined. The impact of SAS, KAS, and HCL on inactivation of major foodborne pathogens were studied. The antimicrobial mode of action of SAS and KAS are depended on pH, oxidation and osmolarity.